Entre Fronteiras: A Emergência da Psicologia Política da Ação Pública como campo Interdisciplinar - Alessandro Soares da Silva (Confins)
We address the issue of public policies from the perspective of the theory of public action. Our intention is to contribute to the theoretical development of this perspective based on contributions from Political Psychology and Political Geography. This allows a greater understanding and mastery of political phenomena, power relations, as well as the subjective aspects that condition the effectiveness of public action.